Establishing boundaries : Christian-Jewish relations in early council texts and the writings of Church Fathers - Boddens Hosang, F. J. E. (Jewish and Christian Perspectives Series, 2010)
This book addresses the ongoing close relations between ordinary Christians and Jews on a daily basis at a time when church leaders were increasingly trying to establish boundaries between Christians and other religious groupings, especially Jews. Until recently, most historical studies of late antique Christian-Jewish relations had been primarily based on the writings of the church fathers.This new study makes use of a new type of source material: fourth to late sixth century council documents in which clear indications are given of the daily relationships between Christians and Jews. The texts from the eastern and western Mediterranean describe contacts between Christianity and Judaism at the level of ordinary people. These contacts remained close for a much longer period than the church leaders would have liked.